New advances in the treatment of atopic dermatitis - WANG Xinyu; ZHANG Guohui (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Atopic dermatitis (AD) is a chronic, recurrent, inflammatory and pruritic skin disease related to genetic allergic predisposition. Traditional treatments mainly include repairing the skin barrier, using topical glucocorticoids and calcineurin inhibitors, systemic therapy and phototherapy. But there are certain limitations because of the difficulty to achieve clinical cure. In recent years, based on the etiology and pathogenesis of AD, biologics and small molecule targeted drugs have been used in the clinical treatment. However, the high cost limits their wide use in clinic. Therefore, some scholars are also attempting to explore other therapeutic regimens such as extracts of traditional Chinese medicinal herbs, allergen immunotherapy, and regulation of microbial homeostasis. Here we review the advances in the treatment of AD.